PENGARUH KINERJA KEUANGAN DAN FINANCIAL DISTRESS TERHADAP KEBIJAKAN DIVIDEN DALAM MASA PANDEMI COVID-19 - Reki Febriano El Rasyid; Darsono Darsono (Diponegoro Journal of Accounting, 2022)
The purpose of this research is to examine the effect of financial distress and financial performance on dividend policy during COVID-19 pandemic. Variabels used in the examination are financial distress, profitability, liquidity, leverage and firm size as the independent variabel and dividend policy as the dependent variabel. The population of this study is manufacturing companies listed in Indonesia Stock Exchange (IDX) during the 2020-2021. Sampling based on purposive sampling method with 113 total sample. Data analysis was performed classical asumption and hypothesis testing using linear regression. The result of this study indicates that profitability have significant positive effect on dividend policy. Meanwhile, financial distress, liquidity, leverage, and firm size shows insignificant effect on divident policy..